2014
DOI: 10.1002/bmc.3284
|View full text |Cite
|
Sign up to set email alerts
|

Resolution and isolation of enantiomers of (±)‐isoxsuprine using thin silica gel layers impregnated with l‐glutamic acid, comparison of separation of its diastereomers prepared with chiral derivatizing reagents having l‐amino acids as chiral auxiliaries

Abstract: Thin silica gel layers impregnated with optically pure l-glutamic acid were used for direct resolution of enantiomers of (±)-isoxsuprine in their native form. Three chiral derivatizing reagents, based on DFDNB moiety, were synthesized having l-alanine, l-valine and S-benzyl-l-cysteine as chiral auxiliaries. These were used to prepare diastereomers under microwave irradiation and conventional heating. The diastereomers were separated by reversed-phase high-performance liquid chromatography on a C18 column with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Chiral derivatizing reagents prepared by substitution of the fluorine atoms in 1,5-difluoro-2,4-dinitrobenzene (DFDNB) with three amino acids: L-alanine, L-valine, and (S)-benzyl-L-cysteine cysteine were used for enantioresolution of racemic β 2 -agonist isoxsuprine on reversedphase HPLC and reversed-phase thin-layer chromatography [117].…”
Section: Indirect Chiral Chromatographic Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral derivatizing reagents prepared by substitution of the fluorine atoms in 1,5-difluoro-2,4-dinitrobenzene (DFDNB) with three amino acids: L-alanine, L-valine, and (S)-benzyl-L-cysteine cysteine were used for enantioresolution of racemic β 2 -agonist isoxsuprine on reversedphase HPLC and reversed-phase thin-layer chromatography [117].…”
Section: Indirect Chiral Chromatographic Separationmentioning
confidence: 99%
“…TLC served for the resolution of enantiomers of isoxsuprine using thin silica gel layers impregnated with L-glutamic acid. The limit of detection of each enantiomer was 11-13 ng/mL [117].…”
Section: Stereoselective Thin Layer Chromatography (Tlc) Of β 2 -Agonmentioning
confidence: 99%
“…ii. The structures optimized for the lowest energy, developed by the same software as mentioned above, of the two diastereomeric derivatives of (±)-isoxsuprine prepared with the FDNP reagent having S-benzyl-L-cysteine (Bhushan & Nagar, 2015) iii. On the similar lines it was interpreted that the L-L diastereomer was retained for lesser time in comparison with the L-D diastereomer of SeMet prepared with FDNP-L-Met .…”
Section: The Lowest Energy Optimized Structuresmentioning
confidence: 99%
“…The lowest energy optimized structures (Figure 7) of the two diastereomeric derivatives (of orciprenaline, for example) showed that in the [( S )‐ l ]‐diastereomer, the hydrophobic groups ‐CH 2 SCH 3 on the stereogenic center of CDR (having S ‐methyl‐ l‐ cysteine) and ‐C 6 H 3 (OH) 2 on stereogenic center of orciprenaline considered to be cis to each other and in the [( R )‐ l ]‐diastereomer, the same two groups have trans ‐type arrangement. The diastereomeric derivative with a cis ‐type arrangement (which is more hydrophobic) interacts more strongly with ODS material of the C 18 column than the trans ‐type arrangement, hence it has a longer retention time. The structures optimized for the lowest energy, developed by the same software as mentioned above, of the two diastereomeric derivatives of (±)‐isoxsuprine prepared with the FDNP reagent having S ‐benzyl‐ l‐ cysteine (Bhushan & Nagar, 2015) supported the cis ‐type arrangement of the hydrophobic groups, i.e. ‐CH 2 SC 6 H 5 on the stereogenic center of CDR and ‐CH 2 OC 6 H 5 present on the stereogenic center of isoxsuprine, respectively, in [(−)‐ l ]‐diastereomer, and trans ‐type arrangement in the [(+)‐ l ]‐diastereomer. On the similar lines it was interpreted that the l ‐ l diastereomer was retained for lesser time in comparison with the l‐ D diastereomer of SeMet prepared with FDNP– l‐ Met (Nagar & Bhushan, 2014).…”
Section: Determination Of Absolute Configuration Separation Mechanismentioning
confidence: 99%
See 1 more Smart Citation